Cadmium Bioavailability Based on Diffusive Gradients in Thin Films Technique and Conventional Chemical Extraction in High Geological Background Soil Area of Northwestern Zhejiang Province, China - Chao WU; Binbin SUN; Xiaomeng CHENG; Dong LIU; Yu QIAO; Ling He; Daoming ZENG (Yankuang ceshi)
BACKGROUNDHigh geochemical background has a greater impact on soil Cd pollution than human activities and is more detrimental to the environment and human health on a regional level. Research shows that the bioavailability of Cd in soil is the key factor to determine its bioavailability and biotoxicity, so it is of great theoretical and practical significance to find an effective method to evaluate the bioavailability of Cd in soil for the safe use and risk control of contaminated agricultural land. Single extraction methods with relatively simple operation and relatively low cost and sequential extraction methods providing morphological distribution feature information, are the most common methods for evaluation of heavy metals bioavailability in soil. In general, the available amount of soil heavy metals obtained by chemical extraction methods can better reflect the level of plant absorption than the total amount. However, chemical extraction methods have some drawbacks, including differences between the extraction principle and crop absorption process, a lack of universality in the extracts, redistribution and re-adsorption during the extraction process, and most notably, the failure to take into account dynamic changes in heavy metal concentrations in the root environment. Diffusive gradients in thin-films (DGT) technique is a new biomimetic in-situ sampling technique, which has been widely used to assess the bioavailability of various elements in soil, water, sediment and other environmental media in recent years. The process of DGT absorbing target elements is similar to plants absorption, which can better reflect bioavailability. However, existing research results using DGT to evaluate soil Cd pollution is mainly based on indoor pot experiments. Exogenous addition of heavy metals to contaminated soil not only has high bioavailability, but also reduces the sensitivity of soil pH and other factors to the bioavailability of heavy metals in soil, which does not accurately represent the complex situation in naturally contaminated soil. It is not clear whether the results of DGT can accurately reflect the bioavailability of soil Cd in high geological background areas. In order to confirm whether DGT technology can effectively evaluate the bioavailability of soil Cd in high geochemical background areas when compared to existing chemical extraction methods, 80 sets of paddy soil-rice and 20 sets of dry soil-bok choy samples were collected in the black shale area of Northwest Zhejiang Province. The DGT technology, 0.01mol/L CaCl2 extraction method, seven-step extraction method and soil solution method were used to evaluate the bioavailability of Cd in soil. Inductively coupled plasma-mass spectrometry (ICP-MS) was used to determine Cd content and available Cd in soil and crop. Soil pH was determined by potentiometry (POT), and soil organic matter (OM) was determined by oxidation combustion potentiometry (POT). The migration and accumulation characteristics of Cd in a soil-crop system were analyzed. The evaluation effects of different bioavailability evaluation methods were compared by the correlation between available Cd and crop Cd content.RESULTS(1) The total content and fraction distribution characteristics of Cd in soil. The results show that the Cd average contents in paddy soil and dry soil in the study area are 1.07mg/kg and 0.73mg/kg, respectively, remarkably higher than the background values of soil in Zhejiang Province and China. The abnormal enrichment of Cd is mainly related to the widespread black shale in Northwest Zhejiang. For the sequential extraction procedures, the average content in paddy soil of water-soluble and exchangeable Cd, carbonate-bound Cd, humic acid-bound Cd, Fe-Mn oxide-bound Cd, strong organic-bound Cd and residual Cd are 54%, 5.9%, 9.3%, 13.5%, 4.2% and 13.2%, respectively. The average content in dry soil of water-soluble and exchangeable Cd, carbonate-bound Cd, humic acid-bound Cd, Fe-Mn oxide-bound Cd, strong organic-bound Cd and residual Cd are 47.2%, 4.6%, 11.5%, 14.3%, 5.5% and 16.9%, respectively. On the whole, the bioavailable component of Cd in the study area accounts for a relatively high proportion. (2) Characteristics of Cd content in crop. The content of Cd in rice seed in the study area ranges from 0.01mg/kg to 3.29mg/kg, with an average of 0.26mg/kg. The Cd content in bok choy ranges from 0.01mg/kg to 0.31mg/kg, with an average of 0.08mg/kg. In comparison to China’s contaminant limit of national food safety standards (GB2762—2017), the over-standard rates of Cd in rice and bok choy are 34% and 10%, respectively. The soil samples are further assessed according to Soil Environmental Quality Risk Control Standard for Soil Contamination of Agricultural Land (GB15618—2018), the Cd over-standard rates of paddy soil and dry soil are 70% and 75%, respectively. The Cd over-standard rate of soil samples is significantly higher than crop samples. Therefore, the bioavailability of Cd in soil should be considered to scientifically evaluate the pollution level of Cd in soil. (3) Assessment of Cd bioavailability in soil by four extraction methods. The DGT technology, 0.01mol/L CaCl2 extraction method, seven-step extraction method and soil solution method are used to evaluate the bioavailability of Cd in soil. The results are as follows: CDGT, \begin{document}$ C_{{\text{CaCl}}_{\text{2}}} $\end{document}, \begin{document}$ C_{{\text{F}}_{\text{1}}\text{+}{\text{F}}_{\text{2}}\text{+}{\text{F}}_{\text{3}}} $\end{document} and \begin{document}$ C_{\text{soln}} $\end{document}(Fig.3). There is a significant positive correlation between Cd-P and available Cd determined by different methods, but the correlation between CDGT and crop Cd content is better than 0.01mol/L CaCl2 extraction method, seven-step extraction method and soil solution method. The correlation between available Cd in paddy soil and rice are \begin{document}$ C_{\text{soln}} $\end{document}>CDGT>\begin{document}$ C_{{\text{CaCl}}_{\text{2}}} $\end{document}>\begin{document}$ C_{{\text{F}}_{\text{1}}\text{+}{\text{F}}_{\text{2}}\text{+}{\text{F}}_{\text{3}}} $\end{document}. The correlation between available Cd in dry soil and bok choy are CDGT >\begin{document}$ C_{{\text{CaCl}}_{\text{2}}} $\end{document}>\begin{document}$ C_{{\text{F}}_{\text{1}}\text{+}{\text{F}}_{\text{2}}\text{+}{\text{F}}_{\text{3}}} $\end{document}>\begin{document}$ C_{\text{soln}} $\end{document}(Table 3).DISSCUSION(1) Results of DGT technique. The available Cd (CDGT) content measured by DGT for paddy and dry soil in the study area ranges from 0.02μg/L to 1.69μg/L and from 0.14μg/L to 1.88μg/L, with average values of 0.78μg/L and 0.62μg/L, respectively (Fig.3). The correlation coefficients between CDGT and Cd-P in paddy soil and dry soil are 0.622 and 0.887, respectively (Table 3), which are larger than \begin{document}$ C_{{\text{CaCl}}_{\text{2}}} $\end{document}, \begin{document}$ C_{{\text{F}}_{\text{1}}\text{+}{\text{F}}_{\text{2}}\text{+}{\text{F}}_{\text{3}}} $\end{document} and Csoln. The DGT technique is superior to the 0.01mol/L CaCl2 extraction method, seven-step sequential extraction method and soil solution method in reflecting soil Cd bioavailability, and the evaluation effect is not affected by land use types. The DGT technique can be used to simulate Cd release process from soil to solution cased by plant root absorption, and reflects the Cd content in crops more accurately than chemical extraction methods. (2) Results of 0.01mol/L CaCl2 extraction method. The available Cd (\begin{document}$ C_{{\text{CaCl}}_{\text{2}}} $\end{document}) content measured by 0.01mol/L CaCl2 extraction method for paddy and dry soil in the study area ranges from 0.07mg/kg to 0.95mg/kg and from 0.08mg/kg to 0.55mg/kg, with average values of 0.58mg/kg and 0.31mg/kg, respectively (Fig.3). The correlation coefficients between \begin{document}$ C_{{\text{CaCl}}_{\text{2}}} $\end{document} and Cd-P in paddy soil and dry soil are 0.583 and 0.795 respectively (Table 3), which shows a good level of correlation. On the whole, its evaluation effect is second only to DGT technology. Studies have shown that \begin{document}$ C_{{\text{CaCl}}_{\text{2}}} $\end{document} solution can effectively replace metal ions adsorbed by soil particles, and the change of soil pH and soil structure has little effect on the replacement rate, giving it a wide range of applications. \begin{document}$ C_{{\text{CaCl}}_{\text{2}}} $\end{document} solution mainly displaces the adsorbed Cd from soil through static ion exchange, and the extracted available Cd is mainly water-soluble and exchangeable Cd, but some bioavailable metals in soil (such as soil particles or unstable organic/inorganic complexes in soil solution) may not be extracted, so the bioavailability of Cd in soil may be underestimated. (3) Results of seven-step extraction method. Compared with the single extraction method, the sequential extraction method provides the speciation characteristics of heavy metals, and can be used to more comprehensively evaluate the mobility, availability and potential toxicity of heavy metals in soil. Water-soluble Cd, exchangeable Cd and carbonate-bound Cd are generally classified as bioavailable components (\begin{document}$ C_{{\text{F}}_{\text{1}}\text{+}{\text{F}}_{\text{2}}\text{+}{\text{F}}_{\text{3}}} $\end{document}). The available Cd (\begin{document}$ C_{{\text{F}}_{\text{1}}\text{+}{\text{F}}_{\text{2}}\text{+}{\text{F}}_{\text{3}}} $\end{document}) content measured by the seven-step extraction method for paddy and dry soil in the study area ranges from 0.08mg/kg to 3.95mg/kg and from 0.13mg/kg to 1.61mg/kg, with average values of 0.64mg/kg and 0.40mg/kg, respectively (Fig.3). The correlation coefficients between \begin{document}$ C_{{\text{F}}_{\text{1}}\text{+}{\text{F}}_{\text{2}}\text{+}{\text{F}}_{\text{3}}} $\end{document} and Cd-P in paddy soil and dry soil are 0.577 and 0.717 respectively (Table 3), which are lower than 0.01mol/L CaCl2 extraction method and DGT technique. The migration factor (MF) is the relative proportion of the bioavailable components \begin{document}$ C_{{\text{F}}_{\text{1}}\text{+}{\text{F}}_{\text{2}}\text{+}{\text{F}}_{\text{3}}} $\end{document} of Cd in the soil. The MF of Cd in paddy soil and dry soil are as high as 59.9% and 51.8%, respectively, which indicate that Cd is easy to migrate and enrich in the soil-crop system. (4) Results of soil solution method. Soil solution (Csoln) is the main place of substance exchange between plants and soil, so it can indicate the bioavailability of heavy metals in soil. The available Cd (Csoln) content measured by soil solution method for paddy and dry soil in the study area ranges from 0.03μg/L to 2.18μg/L and from 0.15μg/L to 2.9μg/L, with average values of 1.22μg/L and 1.99μg/L, respectively (Fig.3). The correlation coefficient between Csoln and Cd-P in paddy soil is larger than CDGT, \begin{document}$ C_{{\text{CaCl}}_{\text{2}}} $\end{document} and \begin{document}$ C_{{\text{F}}_{\text{1}}\text{+}{\text{F}}_{\text{2}}\text{+}{\text{F}}_{\text{3}}} $\end{document}. However, the correlation coefficient in dry soil is the smallest, so the effect of bioavailability evaluation is unstable (Table 3). This is mainly due to the fact that some inert Cd in soil solution cannot be absorbed and utilized by plants, and it is difficult to extract potential available Cd, which has great limitations. (5) A comprehensive evaluation of four extraction methods. Comparing the characteristic and applicability of different methods, DGT technology, single extraction method, sequential extraction method and soil solution method have different application scope and significance, and they all play an irreplaceable role in bioavailability evaluation of soil Cd. There is a significant positive correlation between soil available Cd determined by the four methods and crop Cd, the extraction techniques of soil available Cd can effectively reflect the content level of available Cd in soil. DGT technology can simulate the dynamic absorption process of Cd by plants which can more accurately reflect the bioavailability of Cd in soil. The single extraction method is relatively simple in operation and relatively low in cost, which is mainly used for quickly judging the bioavailability level of Cd in soil. 0.01mol/L CaCl2 is recommended as an extractant for available Cd in soil. The sequential extraction can be used to obtain the speciation characteristics of soil Cd, which focuses on the analysis of available Cd and potentially available Cd in soil. Soil solution can not only reflect the bioavailability of heavy metals, but is also a key parameter for environmental models to predict and quantitatively assess the surface runoff and infiltration of heavy metals in soil.